1, 4-Dicyanobenzene as electrolyte additive for improve electrochemical performance of Li1.2Ni0.2Mn0.6O2 cathode materials in lithium metal rechargeable batteries. (16th January 2022) - Zhuang, Yan; Bao, Yingqing; Zhang, Wei; Guan, Mingyun
Highlights: 1, 4-DCB eliminates the trace water in the electrolyte under acidic conditions. The coating layer formed by 1, 4-DCB oxidized inhibits the decomposition of electrolyte. Group N in electrooxidation product of 1, 4-DCB combines with PF5 to stable LiPF6 . Cyclability and rate capability of battery can be improved by 1, 4-DCB additive. Abstract: The cycling stability of Li1.2 Ni0.2 Mn0.6 O2 cathodes is increased enormously by adding 0.1 %wt 1, 4-dicyanobenzene (1, 4-DCB) additive in the electrolyte, and the capacity retention increases from 20.3% to 63.8% after 350 cycles. It is found that 1, 4-DCB eliminates the trace water in the electrolyte via hydrolysis under acidic conditions. A coating layer on the electrode surface is formed by preferentially oxidized of 1, 4-DCB, which reduce the contact between electrolyte and cathode, inhibiting the decomposition of electrolyte solvent. N group in the electrooxidation product of 1, 4-DCB can combine with PF5 to improve the stability of LiPF6, then reducing the decomposition of LiPF6 . The benzene ring and conjugated bond of 1, 4-DCB are favorable for the transfer of interfacial electron and ion, and then the electrochemical performance of lithium-rich layered materials is improved.